STUDI KOMPARASI PRESTASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER (NHT) DAN THINK PAIR SHARE (TPS) PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMA NEGERI 10 PEKANBARU - Sari, Yeni Yulia; Copriady, Jimmi; Erna, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of research to find out significant differences in student’s achievement and to determine student’s achievement higher between implementation of cooperative learning models NHT and TPS on learning topic of Atomic Structure and Elements of the Periodic System. This is an true experimental research with design Randomized Control Group Pretest-Posttest. Population on this research are all students of class XI IPA SMAN 10 Pekanbaru 2015/2016 academic year consisting of 5 classes. The research sample consisted of 3 classes, XI IPA 1 as the experimental class of NHT, XI IPA 2 as the experimental class of TPS and XI IPA 3 as the control class. Research data analysis using ANOVA one way followed by Scheffe multiple comparison test. Based on the results of data processing by ANOVA one way obtained that Fcount > Ftable is 18,92 > 3,08 with α = 0,05; df JKA = 2 and df JKD = 109. The results of data processing by Scheffe multiple comparison test was obtained the difference between the average experimental class of NHT and TPS exceeded the values Scheffe is 5,6> 4,49 with α = 0,05 and an average experimental class of NHT higher than average experimental class of TPS is 48,96> 43,36. Based on the analysis of data processing concluded that there are significant differences in student’s achievement between implementation of cooperative learning models NHT and TPS. Student’s achievement with implementation of cooperative learning models NHT higher than TPS on learning topic of Atomic Structure and Elements of the Periodic System in class XI IPA SMAN 10 Pekanbaru.Keywords: NHT, TPS, Learning Achievement, Atomic Structure and Elements of the Periodic System